Hysteresis modeling and feedforward compensation of a flexible structure actuated by macro fiber composites using bias bipolar Prandtl-Ishlinskii model. (November 2021) - Xu, Jinqiu; Lou, Junqiang; Yang, Yiling; Chen, Tehuan; Chen, Hairong; Cui, Yuguo
As a novel fiber-based piezoelectric composite material, macro fiber composites (MFC) affords notable advantages of good flexibility, high deformability, and large actuation ability. However, the intrinsic hysteresis behavior of the MFC decreases the positioning precision and performance of the flexible structure actuated by MFC actuators. A bias bipolar Prandtl-Ishlinskii (BBPI) model is presented to describe the bias bipolar hysteresis nonlinearity of a MFC-actuated flexible cantilever. The BBPI hysteresis model is composed of two parts: a superposition of the weighted play operators of the classical Prandtl-Ishlinskii (PI) model is employed to characterize the symmetric hysteresis. And a superposition of the weighted dead-zone operators is cascaded to deal with the bias bipolar behavior. Experimental identification results demonstrate that the presented BBPI model exhibits better modeling performance than the classical PI model. A feedforward compensation strategy based on the inverse BBPI hysteresis model is proposed. Experiments on trajectories tracking subject to a triangular wave, sinusoidal wave, and triangular wave with random amplitudes are carried out. Experimental results demonstrate the feasibility and effectiveness of the proposed BBPI model and the inverse feedforward compensator.